Sensitivity analysis on thermophysical properties efficacy on PCM-based heat sink usefulness: effects of solid particles versus liquid phase fraction - Abu-Hamdeh, Nidal H.; Abusorrah, Abdullah M.; Hosseini, Farnaz; Bayoumi, Mohannad M.; Öztop, Hakan Fehmi (Springer, 2021)
In this study, PCM-based heat sink effectiveness was investigated to examine the role of thermophysical properties. Through sensitivity analysis, the PCM thermophysical properties were changed to investigate the efficacy of each parameter on the objective function. For this purpose, the conservation equations for the PCM filled heat sink were solved using the Green-Gauss finite volume method. There were two interfaces within the PCM-based heat sink. The interface between solid nano-particles and liquid phases was tracked using the enthalpy-porosity approach, while the interface between air and PCM was located using the two-phase VOF technique. It was found that increasing the melting temperature diminished the PCM-filled heat sink effectiveness (keeping the base temperature low). As the thermal conductivity doubled, the PCM-filled heat sink ability in lowering the base temperature was slightly improved. The increase in latent heat led to an increase in melting time and consequently improved the effectiveness.
Keywords: Phase change material; Heat sink; Sensitivity analysis; Thermophysical property